Industrialized building system in construction projects: a study on readiness - Tamrin, Norhidayah; Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar (Medwell Journal, 2017)
This study presents a review of readiness in the Malaysia Industrialised Building System (IBS).IBS has been introduced since 1960 and since then, there are many advantages that can be seen from the implementation of IBS in Malaysia.Although, construction player already know the advantages of IBS but at the same time, implementation of IBS in Malaysia is still in low phase. This study also highlights the obstacles of IBS implementation in Malaysia.Based on literature review there are several obstacles to IBS implementation which are awareness, cost issues, readiness, planning and implementation, negative perception incentive, directive and promotion, knowledge and project delivery and supply chain.Readiness is one of the obstacles and there is limited study of readiness issues for implementing IBS at present.This study is part of on-going Master research on key factor of readiness in IBS implementation.This conceptual study will explore why readiness is important to increase the level of IBS implementation.From the findings, further research into the factor of readiness is highly crucial to provide an insight to the construction industry players in making the transformation from conventional method to IBS a successful effort. Therefore, it is hoped that the finding of this research could assist construction player to ready for implement of IBS then, indirectly it can increase the level of IBS implementation in Malaysia.